Influence of Parenting Styles on Academic Performance of Students in Public Senior Secondary Schools in Gombe LGA, Gombe State - Alfayo , Samuel Boh (Kashere Journal of Education, 2025)
The study used a descriptive research design. A descriptive research design is appropriate when the research aims to identify characteristics, trends, frequencies and categories. The population of the study consists of all the public senior secondary class two (SS 2) students in Gombe LGA. These areas have public senior secondary schools with a total population of 19,011 students. These schools are distributed across North, South, West and East of Gombe Local Government according to the statistical records available in the Post Primary Schools Management Board (PPSMB 2024), Gombe Zone. Out of which 4 public senior secondary schools were selected with a total population of 1996. A sample is a smaller group of elements drawn through a definite procedure from a specified population. The results of the sample survey selected are to truly represent the Population. The sample of this study of 17 public senior secondary schools in the Gombe metropolis of Gombe state was in accordance with the Morgan (1970) table for determining the sample size, since the total population of students in the selected schools is 1996, the sample size of 320 was used. The instrument used for data collection was a questionnaire. The researcher prepared the instrument based on the purpose of the study. The questionnaire has two parts. Part A contains the respondent’s personal identity, while part B contains sections A-D, each representing the purpose of the study and reflected in the research questions. The questionnaire was structured in the form of a four-point Likert scale. In view of the large population of the respondents for the study, the researcher made use of two research assistants for each of the selected schools. The results from the responses show that children of authoritative parents work harder on their academics than others and Item 2 shows that 80% of respondents strongly agreed that children of democratic parents perform very low academically Mean and percentage were used to analyse the research questions posed for the study. It was recommended that, Parents are here by encouraged to improve on their relationship with their children and choose the right Parenting Style that will help their children to perform well in the academic aspects. Parents are expected to practice Authoritative Parenting style in other to help them perform well in their academics, and Parents should practice that kind of parenting style so that their children can improve on their academic Performance